CONVERSION OF FOCAL CHOROIDAL EXCAVATION WITH THE ONSET OF CENTRAL SEROUS CHORIORETINOPATHY: REPORT OF 2 CASES AND REVIEW OF THE LITERATURE. Issue Volume 15:Issues 4(2021) (July 2021) - Docherty, Gavin; Sidiqi, Ahmad; Martens, Rosanna; Akil, Handan; Navajas, Eduardo V.
Abstract : Purpose: To describe two cases of focal choroidal excavation (FCE) conversion in patients with central serous chorioretinopathy. Methods: Case report and literature review of cases of FCE conversion. Results: A 35-year-old asymptomatic pregnant patient was found to have conforming FCE on spectral domain optical coherence tomography of the right eye during hydroxychloroquine screening. Three months later, she presented with decreased vision in the right eye and subretinal fluid in both eyes secondary to central serous chorioretinopathy. Spectral domain optical coherence tomography revealed that her FCE had changed to nonconforming type. A 40-year-old male patient was found to have nonconforming FCE and subretinal fluid in his right eye on spectral domain optical coherence tomography. On follow-up, spectral domain optical coherence tomography demonstrated resolution of subretinal fluid and conversion of nonconforming FCE to conforming type. Literature review showed that most cases of FCE remain stable over time. Conversion from nonconforming FCE to conforming type has been described after photodynamic therapy or anti–vascular endothelial growth factor therapy. Conversion from conforming to nonconforming type has been described in 2 cases that developed subretinal fluid in the setting of acute central serous chorioretinopathy. Conclusion: Our cases and literature review suggest that nonconforming FCE is the result of persistent subretinal fluid. Further studies are necessary to determine whether symptomatic nonconforming SRF needs treatment to reduce subretinal fluid. Abstract : Focal choroidal excavation is a relatively newly recognized entity. It is known to be associated with myopia, central serous chorioretinopathy, choroidal neovascularization, and polypoidal choroidal vasculopathy. In this study, we report 2 cases of acute central serous chorioretinopathy that demonstrated conversion from conforming to nonconforming focal choroidal excavation or vice versa and review the literature for this unique finding.